A Research Landscape on Formal Verification of Software Architecture Descriptions - Araujo, Camila; Cavalcante, Everton; Batista, Thais; Oliveira, Marcel; Oquendo, Flavio (IEEE access, 2019)
One of the many different purposes of software architecture descriptions is contributing to an early analysis of the architecture with respect to quality attributes. The critical nature of many software systems calls for formal approaches aiming at precisely verifying if their designed architectures can meet important properties such as consistency, completeness, and correctness. In this context, it is worthwhile investigating the role of architecture descriptions to support the formal verification of software architectures to ensure their quality, as well as how such a process happens and is supported by existing languages and verification tools. To evaluate the research landscape on this subject, we have carried out a systematic mapping study in which we collected and analyzed studies available at the literature on formal verification of architecture descriptions. This work contributes with (i) a structured overview and taxonomy of the current state of the art on this topic and (ii) the elicitation of important issues to be addressed in future research.